(3cTa GdCSQGQ Yf Mce GdWjhQ hGdCRgGQs - (3YHO GdSdGe Hf CMeO Hf ZGfe GdfGHdSj GdebOSj, YR GdOjf,J (B678 (3g` s
(3ChdgG (B:s
(3hHYO aEfi fXQJ HYjf GdJMbjb hQCjJ HfhQ GdJhajb s
(3BNQgG (B:s
(3cGf dg ai fXQg YHQI aEjGc hGdaJQI hddg GdMeO hGdefI Ydi GdJeGe hGdceGd s
(3cJHJ HQSe NRGfI CMeO Hf eMeO Hf CHj jRjO GdMRei ai HYV UaMGJgG HjGV JQc ceGf GdUhQI hde jUhQ ai (B60 (3hQbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B355 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B571s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B450 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B173 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI dGdG ESeGYjd HGSJGfHhd (B(565) s
Keywords: (3GdcjejGA h GdWHjYjGJs